Changes in sedimentary environment at Kim Son coastal plain - Ninh Binh, North Vietnam - Ha, Vu Van; Quang, Nguyen Minh; Son, Pham Quang; Ban, To Xuan; Dien, Tran Ngoc; Tan, Mai Thanh; Cuc, Nguyen Thi Thu; Tuan, Dang Minh; Min, Nguyen Thi; Tung, Dang Xuan; et al. (Vietnam Journal of Marine Science and Technology, 2021)
Kim Son coastal plain is a part of the Red River Delta located between Day and Can rivers. Over the past 55 years, Kim Son coastal plain has been the region with the highest accretion rate in the Red River Delta. This study aims to clarify the sediment characteristics of Kim Son coastal plain. It has the structure of a typical tidal flat and a relatively straightforward tide-influenced sedimentary structure evidenced by the field observation, sampling 70 hand-drilled boreholes, borehole logging and analyzing 177 samples of grain size. There are three tidal sedimentary zones to be identified, including sand flat, mixed flat, and mudflat. The history of topographic changes is also presented over six periods from 1965 to 2020 based on analyzing and interpreting multi-time satellite images. The total accretion area of Kim Son coastal plain over 55 years was 4,081.2 ha.